The Poison Belt - Doyle, Arthur Conan, 1859-1930 (Salt Lake City, UT : Project Gutenberg, 1994)
"The Poison Belt" by Arthur Conan Doyle is a science fiction novel written in 1913. Professor Challenger summons his companions to his Sussex home with urgent instructions to bring oxygen. He has discovered that Earth is moving into a belt of poisonous ether that threatens to suffocate all life. Sealed in a single room with oxygen cylinders, the group watches helplessly as the world outside succumbs to the deadly phenomenon, leaving them to face an uncertain fate. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Poison_Belt
Release date is 1994-04-01
Keywords: Science fiction; Challenger, Professor (Fictitious character) -- Fiction